Nigerian governments' policies affecting investment in agriculture - Olatunbosun, Dupe. (East Lansing, Michigan ; Ibadan : Consortium for the Study of Nigerian Rural Development in collaboration with Nigerian Institute of Social and Economic Research, 1968)
The objective of this study is to present to the reader such information as exists on incentives or disincentives of agricultural and industrial development in Nigeria
Includes bibliographical references: p. 53.
osc 30/01/2019
Loans
Keywords: Agriculture and state; Capital investments